Entre a alfabetização e o letramento: qual é a visão das professoras do quinto ano do ensino fundamental? - SILVA, Antonirene Rodrigues de Assis (2021)
This dissertation addresses the literacy students in the fifth year of Elementar School in the process of acquisition alphabetic writing. We start from the assumption that literacy and literacy are distinct and the same time inseparable elements, fundamental for the insertion of the subject in the literate society and for the exercise of citizenship. The study was carried out in four schools of the Municipal Education Network of Imperatriz, having as the teachers as subjects of the research, whose general objective was to analyze the understand of the teachers about the literacy process of students of the fifth year of Elementary School. Therefore, the theoretical contributions that supported the work are based especially on the assumptions of Genetic Epistemology (PIAGET, 2009; 1990; 1973; 1977), Psychogenesis of Written Language (FERREIRO; TEBEROSKY, 1994; FERREIRO, 2001, 2010a; 2010b), of literacy and literacy (SOARES, 2000; 2017; 2018a; 2018b; 2020); (TFOUNI, 1995); (PEREIRA, 2007); (CARVALHO, 2005; 2010), among other studies.The paradigm adopted is learning prevailing in teaching and the student as an active learner, constructor of knowledge. This is a qualitative research, in which the following data collection instruments were used: Portuguese language questionnaire for students writing diagnosis and a fictitious classroom case, analyzed in conversation circles with the teachers. The data reveal that some fifth-year students, research informants, have not yet consolidated their alphabetic writing and the teachers understand literacy as a continuous learning that takes place through the teaching process, with a vision focused on the teaching process and the use of the synthetic method. We conclude that in writing hypotheses of each student about the conventions of written language in a exercises of attentive listening, with methodologies that start from the various textual genres, as well as a pedagogical mediation anchored in the student’s learning perspective.